Lessons in teaching reading comprehension in primary schools - Horton, Suzanne; Bingle, Branwen; Beattie, Louise (Lessons in teaching, 2015)
This book provides exemplar lessons in reading for more able pupils in KS2 and uses them as a starting point for learning. It explores the theory behind good lessons, what makes them good and how they can be adapted to suit different classes and different schools.